Development of Problem Solving Based E-Modules Assisted by Flipbook in Physics Learning for Middle School Students - Damaiyanti, Alvina; Silitonga, Haratua Tiur Maria; Hidayatullah, Muhammad Musa Syarif (Jurnal Paedagogy, 2025)
This research aims to create a problem-solving e-module supplemented by a flipbook, for physics education targeting junior high school students. This study employed the research and development (R&D) method utilizing the ADDIE model, encompassing the phases of analysis, design, development, implementation, and evaluation. The research methodologies encompassed observation, interviews, questionnaires, and pre-tests and post-tests. This research employed a data analysis technique that incorporates quantitative and qualitative descriptive analysis, utilizing the Aiken V index for data evaluation. The findings of this study demonstrated that the created e-module possesses a high feasibility level, evidenced by an average validation score of 0.83, classified as very valid. The deployment of the e-module among 28 seventh-grade students in class VII C at SMP Negeri 6 Pontianak yielded an effect size of 3.02, categorizing it as very effective, while the assessment of students' problem-solving abilities revealed an average N-Gain value of 0.53, indicating a modest level of improvement. The teacher's reaction rate was 97%, while the pupils' response rate during the field trial was 86%, both classified as exceptionally high. The results demonstrate that the problem-solving-based e-module, supplemented by a flipbook, is an excellent physics learning medium for enhancing problem-solving skills related to the theme of matter and its transformations.